Mission Animation: Christian Higher Education, the Common Good, and Community Engagement - Mann, Jessica (Christian higher education, 2020)
Christian institutions are founded on a diverse set of historical and theological backgrounds and strive to integrate faith, learning, and living in a way that not only educates and develops students, but also responds to the Christian call of service. Community engagement, therefore, becomes a way for Christian institutions to achieve said goals—fostering authentic partnerships, responding to the needs of communities and individuals, and encouraging student learning and development. This article maps the landscape of community engagement in Christian higher education by exploring its history as well as its philosophical, theological, and theoretical foundations. In addition, practical expressions of community engagement are addressed through a review of two national Christian higher education associations—the Council for Christian Colleges & Universities (CCCU) and the Association of Catholic Colleges and Universities—as well as a consideration of programmatic exemplars at evangelical Christian and Catholic institutions and an accounting of CCCU and ACCU members receiving the Carnegie Classification for Community Engagement. The article concludes with a consideration of how community engagement represents a critical dimension of Christian mission in action for evangelical and Catholic colleges and universities.